Congenital amegakaryocytic thrombocytopenia – Not a single disease. Issue 2 (June 2021) - Germeshausen, Manuela; Ballmaier, Matthias
Abstract: Congenital amegakaryocytic thrombocytopenia (CAMT) is a rare inherited bone marrow failure syndrome (IBMFS) that is characterized by severe thrombocytopenia at birth due to ineffective megakaryopoiesis and development towards aplastic anemia during the first years of life. CAMT is not a single monogenetic disorder; rather, many descriptions of CAMT include different entities with different etiologies. CAMT in a narrow sense, which is primarily restricted to the hematopoietic system, is caused mainly by mutations in the gene for the thrombopoietin receptor ( MPL ), sometimes in the gene for its ligand ( THPO ). CAMT in association with radio-ulnar synostosis, which is not always clinically apparent, is mostly caused by mutations in MECOM, rarely in HOXA11 . Patients affected by other IBMFS - especially Fanconi anemia or dyskeratosis congenita - may be misdiagnosed as having CAMT when they lack typical disease features of these syndromes or have only mild symptoms. This article reviews scientific and clinical aspects of the various disorders associated with the term "CAMT" with a main focus on the disease caused by mutations in the MPL gene.